Edukasi Masyarakat Siaga (Emas) 1.000 Hari Pertama Kehidupan - Gusriani, Gusriani; Wahida, Wahida; Noviyanti, Nur Indah (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2023)
Stunting is a condition of failure to thrive in children under five years old due to chronic malnutrition, especially during the first 1000 Days of Life (1000 HPK). Stunting affects brain growth and development. Stunted children also have a higher risk of suffering from chronic diseases in adulthood. Based on the results of the 2021 SSGI, the prevalence of stunting in Nunukan Regency is the highest in North Kalimantan, reaching 30%. Among the 17 primary healthcare service areas under the Nunukan district health office, the Sedadap primary healthcare service area has one of the highest incidence rates of stunting. Out of 1,817 measured toddlers, 267 (14.7%) were found to be stunted. This is suspected to be due to the lack of knowledge among the cadres and the community about the 1000 HPK concept, insufficient knowledge among cadres and pregnant women about meeting the nutritional needs of toddlers, and partners not knowing about the use of the Kuesioner Pra Skrining Perkembangan (KPSP) as an early detection and screening tool for toddlers' status and development. The proposed solutions to these issues are the provision of education and assistance in filling out the KPSP. The training method employed includes interactive lectures and direct demonstration practices, while the mentoring process involves periodic monitoring to ensure the successful and sustainable implementation of the program. Overall, this community partnership program is a positive step towards preventing stunting. Education, child development monitoring, and mentoring are essential components that have effectively increased the knowledge and awareness of the community. Through understanding and appropriate actions, stunting issues in toddlers can be minimized, enabling future generations to grow and develop optimally.